Surgical treatment of multi-valve heart disease associated with infective endocarditis - Hamidullah A. Abdumadzhidov (Heart Vessels and Transplantation, 2017)
Objective: The aim of the study was to analyze our own experience of diagnosis, choice of tactics and execution of multi-valve surgical correction of heart defects in infective endocarditis (IE).